Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I know this is a very low level question, but I honestly can't remember how this is done. I want to solve for y with this: $$ x = 2.0 \cdot \arctan\left(\frac{\sqrt{y}}{\sqrt{1 - y}}\right) $$ And I thought I could do this: $$ \frac{\sqrt{y}}{\sqrt{1 - y}} = \tan\left(\frac{x}{2.0}\right) $$

But it seems like I've done something wrong getting there. Could someone break down the process to get to $y =$ ?

Again, I know this is very basic stuff, but clearly I'm not very good at this.

share|improve this question
1  
Whay do you think you have done something wrong? You just need to go further –  Henry Dec 14 '12 at 18:10
1  
Hint: sqrt(y)/sqrt(1 - y) = 1/sqrt(1/y - 1) if $y \not = 0$, so do things like squaring, taking reciprocals and adding $1$ to both sides –  Henry Dec 14 '12 at 18:11
    
@Henry So, I'm not wasting my time going further? The reason I thought I was wrong is because I'm plugging all of my steps into WolframAlpha and when I got from that last step to this one, it pumped out a different and MUCH simpler answer. I would love to do it by hand, though. –  RileyE Dec 14 '12 at 18:12
add comment

2 Answers

Two hints:

  • sqrt(y)/sqrt(1 - y) = 1/sqrt(1/y - 1) i.e. $\dfrac{\sqrt{y}}{\sqrt{1 - y}} = \dfrac{1}{\sqrt{1/y - 1}}$ if $y \not = 0$

  • (tan(x/2))^2 = (1-cos(x))/(1+cos(x)) i.e. $\tan^2\left(\dfrac{x}{2}\right) = \dfrac{1-\cos(x)}{1+\cos(x)}$ if $\cos(x) \not = -1$

share|improve this answer
add comment
up vote 2 down vote accepted

So, since Henry told me that I wasn't wrong, I continued and got a really simple answer. Thanks!

x = 2 * arctan(sqrt(y)/sqrt(1 - y))
sqrt(y)/sqrt(1 - y) = tan(x/2)
1/(sqrt(1 - y) * sqrt(1/y)) = tan(x/2)
1/tan(x/2) = sqrt(1/y - 1)
1/(tan(x/2))^2 + 1 = 1/y
y = (tan(x/2))^2/((tan(x/2))^2 + 1)

Thanks again to Henry!

EDIT

Followed by:

y = ((1 - cos(x)) / (1 + cos(x))) / (1 + (1 - cos(x))/(1 + cos(x)))
  = (1 - cos(x)) / ((1 + cos(x)) * (1 + (1 - cos(x))/(1 + cos(x))))
  = (1 - cos(x)) / ((1 + cos(x)) + (1 - cos(x)))
  = (1 - cos(x)) / 2
share|improve this answer
    
You can do even better with my second hint –  Henry Dec 14 '12 at 18:29
    
@Henry Am I still on the right track? –  RileyE Dec 14 '12 at 18:39
    
I would made the second line ((1 - cos(x))) / ((1 + cos(x)) + (1 - cos(x))) which is (1-cos(x))/2 –  Henry Dec 14 '12 at 21:06
    
@Henry Eesh. I wrote it up on the computer and completely missed that. Good call! –  RileyE Dec 14 '12 at 21:19
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.